1994
DOI: 10.1161/01.atv.14.10.1581
|View full text |Cite
|
Sign up to set email alerts
|

Higher plasma lipid transfer protein activities and unfavorable lipoprotein changes in cigarette-smoking men.

Abstract: The mechanisms responsible for the atherogenic lipoprotein changes associated with cigarette smoking are largely unknown. Lecithin: cholesterol acyltransferase (LCAT) and cholesteryl ester transfer protein (CETP) are key factors in the esterification of plasma cholesterol and the transfer of cholesteryl ester from high-density lipoproteins (HDLs) toward very-low-and low-density lipoproteins (VLDLs+LDLs). Another transfer factor, phospholipid transfer protein (PLTP), recently has been shown to be involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 36 publications
5
63
2
Order By: Relevance
“…The median levels of cholesterol, HDL, LDL, lipoprotein A, APOA1 and APOB are shown in table 3 [Dahlen et al, 1986;Dullaart et al, 1994;Foger et al, 1994;Sandkamp et al, 1990;Walldius et al, 2001] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median levels of cholesterol, HDL, LDL, lipoprotein A, APOA1 and APOB are shown in table 3 [Dahlen et al, 1986;Dullaart et al, 1994;Foger et al, 1994;Sandkamp et al, 1990;Walldius et al, 2001] .…”
Section: Resultsmentioning
confidence: 99%
“…The plasma APOA1 concentration is lower in smokers than in nonsmokers, and exercise training increases the plasma level of APOA1 [Dullaart et al, 1994;Foger et al, 1994]. Several epidemiological studies have revealed an inverse relationship between coronary artery disease and the plasma APOA1.…”
mentioning
confidence: 99%
“…Lifestyle factors further complicate this issue: it has been described that alcohol abuse and physical exercise, typically associated with increased HDL-c, are associated with diminished CETP concentration (55,71,72). Similarly, smoking (associated with low HDL-c) is associated with high CETP activity (73,74). A cross-sectional study showed an inverse relation between CETP and HDL-c among hypertriacylglycerolemic but not normotriacylglycerolemic men (75).…”
Section: Cetp and Dyslipidemia Which Comes First?mentioning
confidence: 99%
“…In a normolipidemic population, the plasma CETP concentration varies mostly over a threefold range and is influenced by environmental factors (6). Plasma CETP has been shown to be elevated in smokers and to be decreased by heavy alcohol drinking and physical training (7)(8)(9).…”
mentioning
confidence: 99%